ANALISIS PENGARUH ALOKASI DANA TERHADAP UMKM PADA BANK SYARIAH - Cantika Wulandari; Okta Debby Anggraini; Ahmad Rusdiwantoro; Putri Nuraini (Jurnal Riset Multidisiplin Edukasi, 2026)
Islamic banking plays a strategic role as a financial intermediary that channels public funds to the real sector based on sharia principles. One of the main sectors targeted for financing is Micro, Small, and Medium Enterprises (MSMEs), considering their significant contribution to the national economy, employment creation, and poverty reduction. However, the level of MSME financing in Islamic banks is strongly influenced by the policies and effectiveness of fund allocation implemented by the banks. Therefore, this study aims to analyze the effect of fund allocation on MSME financing in Islamic banking. The results of the study indicate that the allocation of Islamic bank funds, sourced from Third Party Funds (TPF), investments, social funds, and liquidity management, has a significant influence on the level of MSME financing. Effective and well-targeted fund allocation is able to increase the capacity of MSME financing, encourage business growth, and strengthen the role of Islamic banks in supporting economic development based on justice and public welfare. Thus, optimizing fund allocation is a crucial factor in enhancing MSME financing in Islamic banking.